Assistive Technology in the Classroom: Enhancing the School Experiences of Students with Disabilities - Dell, Amy G.; Newton, Deborah A.; Petroff, Jerry G. (Pearson Merrill Prentice Hall, 2008)
Keywords: Educational technology; United States; United States; Students with disabilities; dept.sed; faculty_collection

Comparing teachers' literacy-related knowledge to their state's standards for reading - McCombes-Tolis, Jule; Feinn, Richard (Reading Psychology, 2008)
This study compared elementary and special education teachers' knowledge of when K-3 students develop key reading competencies, their knowledge of who is responsible for teaching K-3 students key reading competencies, and teachers' perceptions of their own instructionally relevant competencies to those standards articulated within their state's blueprint for reading achievement. Results reveal a disconnect between teacher-held beliefs and state-articulated grade-level student literacy competencies. Results also suggest that teacher preparation programs are not preparing candidates to achieve mastery of essential teacher competencies articulated within their state's reading blueprint. Strengthening the accountability of teacher preparation practices to states' reading blueprint standards is recommended. Copyright © Taylor & Francis Group, LLC.
Keywords: dept.sed

School-wide intervention in the childhood bullying triangle - Mcnamee, Abigail; Mercurio, Mia (Childhood education, 2008)
Keywords: dept.sed

Effective Social Interaction Strategies for Inclusive Settings. - Terpstra, Judith; Tamura, Ronald (Early Childhood Education Journal, 2008)
Many strategies and interventions exist in the education of young children with disabilities. One area of intervention is that of social interaction, including social skills instruction, peer interaction strategies, and play skills. Interaction and social skill strategies for use with children with and without disabilities for the purpose of increasing social interactions between children with and without disabilities in educational settings is an area many educators of early childhood special education strive to find in an effective and easy to implement format. Several strategies from research are presented in this article. Only strategies that were demonstrated to be successful through reported research are discussed. Strategies are identified according to their ease of implementation and effectiveness., (C)2008 Kluwer Academic Publishers
Keywords: Peer interaction; Play skills; Play strategies; Social interaction; Social skills; Social strategies; dept.sed